October Flower, Polygonella polygama - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS, 2018)
October flower is widespread throughout Florida and more broadly in coastal states west to Texas and northeast to Virginia. October flower is found in dune and scrub plant communities and ruderal areas. The showy flowers and attractive foliage make this native plant a desirable ornamental for landscapes. https://edis.ifas.ufl.edu/sg181